Cohesion : a scientific history of intermolecular forces - Rowlinson, J. S. (John Shipley), 1926- (Cambridge University Press, 2002)
"Why does matter stick together? Why do gases condense to liquids, and liquids freeze to solids? This book provides a detailed historical account of how some of the leading scientists of the past three centuries have tried to answer these questions." "The topic of cohesion and the study of intermolecular forces has been an important component of physical science research for hundreds of years. This book is organised into four broad periods of advance in our understanding. The first three are associated with Newton, Laplace and van der Waals. The final section gives an account of the successful use in the 20th century of quantum mechanics and statistical mechanics to resolve most of the remaining problems." "Throughout the last 300 years there have been periods of tremendous growth in our understanding of intermolecular forces but such interest proved to be unsustainable, and long periods of stagnation usually followed. The causes of these fluctuations are also discussed." "The book will be of primary interest to historians of science as well as physicists and physical chemists interested in the historical origins of our modern-day understanding of cohesion."--Jacket